De lo visible a lo oculto: un estudio de visibilidad (SIG) en la región de Vilcabamba, Andes peruanos, durante los periodos Intermedio Tardío y Horizonte Tardío - Conrad, Claire (2024)
The prehispanic Andes are an environment teeming with living beings, both human and non-human. Non-human entities exhibit many similar traits to Andean societies, including a hierarchy, characters with individual personalities and motivations. Regular interactions between humans and these entities were necessary to protect against them. Especially the most important entities, the highest peaks called apus, were potential protectors, but also a constant threat. Visibility and sight are an important aspect in the relationship, as anything within sight of an apu could be considered under its influence and thus could receive a positive or negative impact depending on its mood. This article focuses on that connection between Andean communities and the powerful apus, and how the Inca state could have used architecture to disrupt it using the example of the Vitcos valley. After the incorporation of the Vilcabamba region into the Tawantinsuyu, the Incas built Vitcos as their administrative and religious center and the former larger site Viracochan was abandoned. This meant moving a high-altitude settlement to the valley floor, changing the area that was visible to humans on a daily basis and impacting their communication with the apus of the Cordillera Vilcabamba.